Acrylamide causes neurotoxicity by inhibiting glycolysis and causing the accumulation of carbonyl compounds in BV2 microglial cells. (May 2022) - Wang, Fan; Fan, Ben; Chen, Chao; Zhang, Wensheng
Abstract: Acrylamide is a potent neurotoxin produced during industrial production or food processing at high temperatures, and its effect on glycolytic processes may be critical in triggering neurotoxicity. Our work investigated the neurotoxic effects of acrylamide based on glycolysis using immortalized mouse microglia cell line BV2. The results showed that 1.5 mM acrylamide significantly inhibited the expression and activity of triphosphate isomerase and 3-phosphoglyceraldehyde dehydrogenase. Moreover, acrylamide limited the expression of pyruvate kinase and the decrease of pyruvate and lactate content of glycolysis products. In addition, acrylamide could increase intracellular methylglyoxal content and further affect its detoxification system. Not only that, subsequent cellular responses resulting from methylglyoxal accumulation, such as oxidative stress, activation of ERK, upregulation of NF-κB inflammatory signaling pathway, and elevated pro-inflammatory factor TNF-α, were found in the acrylamide-treated cell model. Therefore, we suggest that acrylamide's perturbation of the glycolytic process leads to methylglyoxal accumulation, which may be responsible for its key to neurotoxicity. Highlights: Acrylamide causes elevation of methylglyoxal by inhibiting the activity of TPI and GAPDH. Acrylamide inhibits pyruvate kinase and leads to a decrease in the amount of pyruvate. Methylglyoxal, as a highly reactive endogenous toxic substance, can exacerbate oxidative stress damage to cells. Oxidative stress causes activation of ERK and NF-κΒ. NF-κΒ enters the nucleus to initiate transcription of TNF-α.